Integrating Health Services in Ontario Through Mergers and Centralization - Krithika Ragupathi (McMaster University Library Press, 2020)
On 18 April 2019, the Legislative Assembly of Ontario passed Bill 74, The People's Health Care Act, which provided new authorities to the Ministry of Health and a newly created Ontario Health super agency to facilitate the integration of health care services across Ontario. This reform represents a shift away from the previous regionalized system of Local Health Integration Networks (LHINs). While centralization is intended to improve efficiency within the system and create a patient-centred model of care, it also equips the Ministry and Ontario Health with greater authority over health agencies. Ontario's reform represents another move towards centralization in a wave of regionalization reversal that has swept across the country. Implementation of this reform will take several years to roll out. An analysis of centralization reforms in other jurisdictions can provide insight into Ontario's decision to reform. Though this bill was presented as a modernization of Ontario's health system to meet people's needs, a common theme in stakeholders' opinions is the lack of consultation with the public. Le 18 avril 2019, l'Assemblée Législative de l'Ontario a mis voté le projet de loi 74, sur les soins de santé pour la population, conférant de nouveaux pouvoirs au Ministère de la Santé et à une toute nouvelle Agence Ontarienne de la Santé pour faciliter l'intégration des services de santé en Ontario. Cette réforme vient remplacer le précédent système régionalisé de réseaux locaux d'intégration des services de santé. Bien que la centralisation vise à améliorer l'efficacité au sein du système et à créer un modèle de soins axé sur le patient, elle confère également au Ministère et à Santé Ontario une plus grande autorité sur les organismes de santé. La réforme de l'Ontario représente un autre pas vers la centralisation suivant la vague d'inversion de la régionalisation partout au pays. La mise en oeuvre de cette réforme se fera sur plusieurs années. Une analyse des réformes de centralisation dans d'autres juridictions peut donner une décision de l'Ontario de se réformer. Malgré le fait que ce projet de loi soit présenté comme une modernisation du système de santé de l'Ontario pour répondre aux besoins des citoyens, les parties prenantes partagent un thème commun dans leurs opinions: le manque de consultation du public.